Firm shutdown during the financial and the sovereign debt crises: Empirical evidence from Portugal - Ferreira, Priscila (2017)
This paper examines Portuguese firms’ survival over the business cycle and investigates whether the effect of firm size varies across the phases of the cycle and with the type of shock associated with periods of economic contraction. Our results show that smaller firms are more likely to shut down than larger firms. Within each size band, however, we found that during the two crises examined, micro firms experienced hazards of closing (relative to large firms) at least similar to those observed in the pre-crisis period, while medium-sized firms were found to have been more vulnerable during the financial crisis period but showed more resilience during the sovereign debt crisis. The results suggest that during the sovereign debt crisis, firms faced a higher probability of closing than they did during the financial crisis.